Kesadaran Anti-Fraud dan Pengendalian Internal terhadap Pencegahan Fraud dalam Pengelolaan Dana Sekolah - Prajanti, Fina Dwi; Hari, Kurnia Krisna; Sabrina, Nina; Basuki, Rahmat (JURNAL ECONOMINA, 2024)
This research aims to determine the effect of anti-fraud awareness and internal control on preventing fraud in senior high schools in the city of Palembang. This type of research is associative research, the data used is primary and secondary data. Data collection methods include interviews and questionnaires. The data analysis technique uses the For Special Science (SPSS) program. The research results show that anti-fraud awareness and internal control together have an effect on preventing fraud. Anti-fraud awareness influences fraud prevention and internal control influences partial fraud prevention.